Atlas of Esophageal Disease and Intervention A Multidisciplinary Approach - Blackmon, Shanda H.; Blackmon, Shanda H.; Kim, Min P.; Kim, Min P.; Dickinson, Karen J.; Dickinson, Karen J. (Springer New York : Imprint: Springer, 2015)
This atlas provides a comprehensive, state-of-the-art review of all interventions that pertain to the esophagus. It includes a review of the current staging modalities, ablation technologies, resection and reconstruction techniques, and disease classification. Evidence-based guidelines regarding how each intervention is chosen are also included. With color illustrations and photographs for each surgery, the atlas details specific anatomic topics such as micro-anatomy of Barrett’s and Dysplasia, EMR pathology, endoscopic ultrasound, and conventional surgical anatomy. Each intervention is presented in task format as a task list to be checked-off as each step is completed. Written by experts in the field, Atlas of Esophageal Disease and Intervention: A Multidisciplinary Approach serves as a valuable resource for any practitioner who performs esophageal intervention and will guide new surgeons and gastroenterologists into the hybrid multidisciplinary approach to this disease.